2012
DOI: 10.1088/0967-3334/33/12/2033
|View full text |Cite
|
Sign up to set email alerts
|

A wireless body measurement system to study fatigue in multiple sclerosis

Abstract: Fatigue is reported as the most common symptom by patients with multiple sclerosis (MS). The physiological and functional parameters related to fatigue in MS patients are currently not well established. A new wearable wireless body measurement system, named Fatigue Monitoring System (FAMOS), was developed to study fatigue in MS. It can continuously measure electrocardiogram, body-skin temperature, electromyogram and motions of feet. The goal of this study is to test the ability of distinguishing fatigued MS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
(60 reference statements)
0
7
0
2
Order By: Relevance
“…Fatigue and autonomic abnormalities, such as cardiovascular or bladder dysfunctions, are frequent symptoms in multiple sclerosis decreasing a patient’s quality of life. Both, fatigue and autonomic abnormalities, occur in early stages of MS and some studies reported an association between fatigue and autonomic abnormalities in MS patients which might indicate a common pathological mechanism underlying these symptoms ( 1 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue and autonomic abnormalities, such as cardiovascular or bladder dysfunctions, are frequent symptoms in multiple sclerosis decreasing a patient’s quality of life. Both, fatigue and autonomic abnormalities, occur in early stages of MS and some studies reported an association between fatigue and autonomic abnormalities in MS patients which might indicate a common pathological mechanism underlying these symptoms ( 1 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of such sensors is that they can be used for long term data monitoring at home or at work to better assess improvement or deterioration. For instance, Yu et al [98] developed a wireless Fatigue Monitoring System (FAMOS), to monitor physiological and functional parameters like ECG, EMG, body-skin temperature and motion. This system was capable of recording data during cognitive and functional tests, as well as during activities of daily living.…”
Section: Multimodal Fatigue Detection and Analysismentioning
confidence: 99%
“…In summary, it is clear from these studies that fatigue is a very important aspect of MS, and that it needs more research to build assessment and monitoring systems. Although several wireless sensor-based setups were developed [95,97,98] , it is still the general consensus that subjective measures generally give a more accurate measure of fatigue a person experiences, regardless of the drawbacks. Several researchers propose a task based framework to monitor fatigue while performing a physical or cognitive task [101].…”
Section: Multimodal Fatigue Detection and Analysismentioning
confidence: 99%
“…In a small group of MS patients compared to controls, FAMOS was associated with fatigue suggesting a link between the symptom and autonomic dysfunction. [45,46] MS is also associated with cognitive impairment but the relation to cognitive fatigability is not clear. While self-reported fatigue has not predicted cognitive performance on a variety of measures, [47,48] it has been linked to cognitive processing speed.…”
Section: Fatigue: Biomedicine Health and Behaviormentioning
confidence: 99%